Room for a Specialist?. (June 2022) - Sherrey, Helen; Forbes, Georgina; Mullan, Helen
When the Associate Specialist grade shut in 2008 it left an untenable situation in which some Specialty Doctors were providing the most senior levels of care for patients without recognition of that seniority. Hence in 2021, the Specialist Grade was created as a new national grade for senior specialist and specialty (SAS) doctors. The post provides autonomous working and recognition of seniority for SAS doctors. Becoming a Specialist Grade doctor is not an automatic career progression and must be applied for when a position is created by the employer. The Specialist Grade route has potential to be an alternative but equally rewarding career choice to traditional training.